Avaliação da ocorrência da estomatite vesicular a partir das notificações de suspeita de síndrome vesicular no estado do ceará, brasil - Rocha, Célio Souza da (2018)
Vesicular stomatitis has socioeconomic importance because it is considered a zoonosis and negatively interferes in the herd with reduction of milk production and weight loss leading to early slaughter. The clinical signs are indistinguishable from those caused by the foot-and-mouth disease virus, so it continues to be classified by the Ministry of Agriculture, Livestock and Food Supply as a disease which requires immediate notification of any suspected cases, and this notification is mandatory for any citizens and practitioners who deal with diagnosis, teaching or animal health research. Therefore, this study aimed to investigate the occurrence of vesicular stomatitis foci by analysing suspected cases of vesicular syndrome reported to the Official Veterinary Service of the State of Ceará - Brazil. During the period from 2013 to 2015, 51 out of suspected cases of vesicular disease were reported. Samples of blood serum, epithelium and esophagus-pharyngeal fluid were collected according to the characteristic of the injuries found and sent to the National Agricultural and Livestock Laboratory - LANAGRO. In addition, an epidemiological survey was performed to identify probable risk factors for the occurrence of the disease. After laboratory and epidemiological diagnosis, 24 properties had foci. It was possible to detect the presence of vesiculovirus type 3 Indiana by 50% complement fixation in 8 outbreaks. No risk factors were identified for the occurrence of the disease when we analysed only the probable cases with laboratory diagnosis. However, there were significant differences between foci and non-foci when we analysed all the suspected cases. The results showed that the occurrence of Vesicular Stomatitis foci in the State of Ceará was related to specific risk factors such as Kind of breeding, uses neighbors' facilities or equipment or vice versa, uses labor from neighbors or vice versa, animals of the establishment participate in agglomeration events and Proximity to properties with motorways, dumps, airports, cold stores, dairy, among others when the epidemiological criteria were taken into account. However, such findings can only be taken into account for the purpose of epidemiological investigation of suspected cases and risk mitigation. Therefore, further studies are needed to describe the transmission of this infectious agent among the susceptible herds in the State through the strengthening of the health defense system